Nigeria’s Economic Challenges and the Hope of Restoration: A Socio-Theological Reading of Psalm 126:1–6 - David Oluwabukunmi Ogunbiyi (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2026)
Nigeria is a multicultural nation endowed with abundant human and natural resources, yet it currently faces profound economic crises marked by high inflation, unemployment, underemployment, widespread poverty, and social instability, particularly banditry and insurgency. This study examines a socio-theological interpretation of Psalm 126:1–6 in the context of these economic challenges and evaluates how the biblical theme of restoration can inspire hope and positive action among Nigerian citizens. Drawing on classical and Keynesian economic theories alongside biblical exegesis of Psalm 126, the study employs a mixed-methods approach using data from 620 Nigerian Christians to analyze the spiritual, emotional, and socio-economic impacts of the crisis. The findings show that the majority of respondents perceive a direct link between Christian faith and socio-economic resilience, viewing Psalm 126 as a source of national encouragement and as a framework for prayer that integrates divine intervention, human responsibility, and aspirations for national development. The study concludes that churches can play a crucial role in national restoration through spiritual support, socio-ethical advocacy, and community development, and recommends stronger governance, church-led social initiatives, and the integration of moral and theological values into policy-making as key pathways toward socio-economic recovery and holistic restoration in Nigeria.